CINNAMATE DERIVATIVE NATURAL COMPOUNDS POTENTIAL AS TYROSINE KINASE INHIBITOR VEGFR-2 - Raihan Firdaus, Hafidh
Most of the deaths in the world today are caused by cancer. One of the causes of cancer is due to the abnormal development of angiogenesis which is regulated by the protein VEGFR-2 (Vascular Endothelial Growth Factor Receptor-2). Some commercial drugs that have been approved by the FDA (Food and Drug Administration) can inhibit VEGFR-2, but their use causes other problems such as side effects and drug resistance. Therefore, the development of natural compounds as VEGFR-2 inhibitors is still being pursued. This research aims to determine the potential of epoxyquinophomopsin A and B compounds, cinnamic acid derivatives, and benzamide derivatives as VEGFR- 2 inhibitors related to anticancer using the molecular docking method. Autodock Vina program is used for docking simulation and genetic algorithm is used as search algorithm. Based on the results obtained, it is known that cinnamic acid derivative compounds have potential as VEGFR-2 inhibitors with docking scores ranging from - 8.2 kcal/mol to -8.4 kcal/mol. The residue interactions that are key to inhibiting VEGFR-2 are Glu885, Asp1046, and Cys919 as backbone residues, Val916 as gatekeeper residues, Val848 and Leu1035 as catalytic residues. This candidate inhibitor compound can be further modified to increase its affinity and bioactivity against VEGFR-2.